A vasculitis centre based management strategy leads to improved outcome in eosinophilic granulomatosis and polyangiitis (Churg–Strauss, EGPA): monocentric experiences in 150 patients. Issue 6 (11th August 2012) - Moosig, Frank; Bremer, Jan Phillip; Hellmich, Bernhard; Holle, Julia Ulrike; Holl-Ulrich, Konstanze; Laudien, Martin; Matthis, Christine; Metzler, Claudia; Nölle, Bernhard; Richardt, Gert; Gross, Wolfgang L
Abstract : Objective: To evaluate a vasculitis centre based management strategy for eosinophilic granulomatosis and polyangiitis (Churg-Strauss, EGPA). Methods: A retrospective cohort study at a vasculitis referral centre was performed. All EGPA patients admitted from 1990 to 2009 were included. A structured interdisciplinary work-up for proof of diagnosis, Disease Extent Index and Birmingham Vasculitis Activity Score was performed. Immunosuppressive therapy was initiated and regularly adapted. Treatment targets were induction and maintenance of remission according to definitions given by the European League Against Rheumatism and the European Vasculitis Study Group. Outcomes were mortality, rate of remission, relapses, adverse events and prednisolone-dose. Results: Out of 269 patients with suspected EGPA 150 fulfilled the inclusion criteria. Of those, 104 had more than one follow-up visit resulting in a mean follow up of 53±4.9 months. By using additional data sources the follow-up concerning survival was extended to 92±5 month. Severe organ manifestations occurred at heart (46%), kidney (18%) and lungs (10%). Cyclophosphamide was used in 107 patients (71%). The prednisolone-doses of all patients were within the targeted range (i.e. ≤7.5mg) in 69% of the total follow-up time; the median dose at end of follow-up was 5mg/d. The 10-year survival rate was 89% resulting in mortality comparable to the general population (SMR 1.29). Only patients with cardiac failure associated with EGPA had an increased mortality (SMR 3.06). Conclusions: Regular re-evaluation and target-orientated adaption of therapy may lead to normalization of life expectancy and attenuation of disease progression. Continued centre based interdisciplinary treatment should be standard of care.